ORMDL3 modulates airway epithelial cell repair in children with asthma under glucocorticoid treatment via regulating IL-33. (October 2020) - Li, Yaqin; Li, Xiaoyan; Zhou, Wenjing; Yu, Qing; Lu, Yanming
Abstract: Background: Study found that glucocorticoids, as first-line treatments for asthma, fails to prevent asthma recurrence. Orosomucoid-like (ORMDL) 3 is associated to childhood asthma onset and involved in the inflammation and repair of airway epithelium. We explored the functional role of ORMDL3 in glucocorticoid treatment for childhood asthma. Methods: Mice were sensitized with Ovalbumin (OVA) and treated with Dexamethasone (Dex), followed by OVA challenge to establish a mouse model of asthma. Histopathological changes in lung tissues were observed by hematoxylin-eosin and masson staining. Human bronchial epithelial (16HBE-14°) cells were transfected with ORMDL3 overexpression plasmid and siRNA-interleukin (IL)-33 alone or in combination, followed by Dex. Cell viability was measured by MTT assay. Cell migration was evaluated by wound healing assay. The expressions of E-cadherin and Vimentin and the activation of NF-κB and MAPK/ERK in 16HBE-14° cells were assessed by Western blot. The expressions of ORMDL3 and IL-33 in lung tissues and 16HBE-14° cells were analyzed by qRT-PCR or Western blot. Results: Dex treatment alleviated the histopathological abnormality and reversed the overexpressions of ORMDL3 and IL-33 in the lung tissues of asthmatic mice. Overexpressed ORMDL3 enhanced migration and viability, decreased E-cadherin level, increased the levels of IL-33 and Vimentin, and promoted the phosphorylation of NF-κB and MAPK/ERK in Dex-treated 16HBE-14° cells, thus reversing the effect of Dex treatment. However, siRNA-IL-33 inhibited viability and migration, increased E-cadherin level, decreased Vimentin level, and suppressed the phosphorylation of NF-κB and MAPK/ERK, thus reversing the effect of overexpressed ORMDL3 in Dex-treated 16HBE-14° cells. Conclusion: ORMDL3 overexpression helped airway epithelial cellrepairin asthma via regulating IL-33 expression.